REVISITING THE BIPOLAR DISTINCTION IN THE CHARACTERISATION OF ARMED CONFLICTS (The Pretoria Student Law Review, 2021)
Since the Geneva Conventions, the architecture of International Humanitarian Law (IHL) has been founded upon a distinction between international armed conflict and non-international armed conflict. Today, this claim stands to be revisited since international and non-international armed conflicts are no longer strict organising frameworks for the categorisation of rules of armed conflicts. This is seen in that over fifty years ago, when the four Geneva Conventions were negotiated, the principles of sovereignty and non-intervention were the cornerstones of international law and while their force today is still apparent, the interdependence of states, and global concerns such as terrorism and the commission of widespread human rights violations have eroded the traditional inviolability of borders. The dichotomy in humanitarian law is as implausible today as it is also fundamentally unworkable given the current conditions of conflicts. This dualist conception is no longer adequate to deal with current features of armed conflict, which do not fit neatly into the two categories and frequently contain mixed elements which thus make the task of classification highly complex. The codification of customary rules of international humanitarian law has narrowed the grounds on which the distinctions are predicated. In addition, the two regimes apply simultaneously on multiple situations. Moreover, the question of contemporary armed conflicts raises serious doubts as to whether the traditional understanding of international law still suffices to explain the complexities of modern day armed conflicts. This essay seeks to offer a different perspective on armed conflicts by suggesting a systematic rethinking of the categorisation of conflict. It argues that some of the dilemmas of contemporary conflicts may be attenuated by a new conceptualisation of this bipolar distinction namely a need for a unitary conception of armed conflict.
Keywords: Geneva Conventions; International Humanitarian Law; codification of customary rules; armed conflicts; principles of sovereignty; non-intervention; non-international armed conflicts